Improving soil properties and maize yield under fertilizer reduction using bio-organic matter combined with biochar - Wang, Juan; Shi, Danyi; Wang, Rui; Zhai, Biyu; Liu, Chuncheng; Feng, Shaoyuan (International Journal of Agricultural and Biological Engineering, 2025)
The harmless treatment of livestock and poultry reduces the risk of water and soil pollution caused by untreated discard of sick and dead livestock. Chemical fertilizer increases crop yield, while its over-application will lead to serious problems such as agricultural non-point source pollution as well as land acidification and soil compaction. It is of great significance to explore the utilization potential of bio-organic matter originating from harmless treatment of livestock to improve the soil environment and enhance agricultural productivity. This study investigated the effects of different application rates of bio-organic matter (0, 1285, 1928, 2571 kg/hm2) and biochar addition (0, 10 000 kg/hm2) on soil properties and crop yield under 20% reduction of chemical nitrogen fertilizer. The results indicated that the application of bio-organic matter combined with biochar improved soil physical structure under fertilizer reduction by decreasing soil bulk density and increasing soil porosity and soil aggregate stability. Compared to that under CK, the soil bulk density was reduced by 1.42%-6.38%, and the soil porosity was increased by 1.17%-7.05%. Compared to conventional fertilization, applying bio-organic matter (1 928 kg/hm2) ensured sufficient soil nutrients for crop growth under 20% of fertilizer reduction. The soil fertility was further boosted by the addition of biochar. The alkaline nitrogen content peaked under BM3 with 42.08 mg/kg, and the total nitrogen content and soil organic matter content reached their peak values under NM4 treatment, which were 0.97 g/kg and 21.23 g/kg, respectively. The higher the amount of bio-organic matter applied, the higher the grain yield and crop water productivity. The yield gained with bio-organic matter application alone at the rate of 2571 kg/hm2 under fertilizer reduction (NM4) was 7504 kg/hm2, which can reach equal yield level with CK, while medium to high addition of bio-organic matter combining biochar (BM3 and BM4 treatments) produced higher grain yield than that under CK. The correlation analysis showed significant positive correlations between total nitrogen and maize yield and between soil organic matter and maize yield. Overall, under 20% fertilizer reduction, applying bio-organic matter at the rate of 1928 kg/hm2 and combining biochar at the rate of 10 000 kg/hm2 would be an economical plan to enhance soil physicochemical properties and ensure stable maize yield, and would also supply a scientific way to reuse bio-organic matter originating from harmless treatment of livestock carcasses. Key words: fertilizer reduction; harmless treatment of livestock carcasses; soil aggregate; soil improvement; maizeDOI: 10.25165/j.ijabe.20251802.9193Citation: Wang J, Shi D Y, Wang R, Zhai B Y, Liu C C, Feng S Y. Improving soil properties and maize yield under fertilizer reduction using bio-organic matter combined with biochar. Int J Agric & Biol Eng, 2025; 18(2): 179–188.